2020
DOI: 10.1021/acs.langmuir.0c01516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Solution-Stable End-to-End Linked Gold Nanorod Dimers via pH-Dependent Surface Reconfiguration

Abstract: End-to-end dimers of gold nanorods are predicted to be excellent substrates for surface-enhanced spectroscopy. However, the synthesis of solution-stable end-to-end dimers remains challenging. We exploit the pH-dependent configurational change of polyelectrolytes to initiate and terminate the gold nanorod assembly formation to produce endto-end linked dimers in high yield. The gold nanorods are first overcoated with a polyelectrolyte, and the end-to-end attachment is initiated by adding a thiol linker in acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Extinction spectra and ζ potential measurements (Figure 1e) confirmed the binding of PAA8k to the nanorod surface. There was a small blue shift in the extinction spectra (Figure 1a, blue), which was consistent with previous reports, 28,29 and the surface charge changed from +24.6 to −60.2 mV upon PAA8k coating. The reversal in the ζ potential sign is due to the presence of carboxylate −COO − groups in the polyelectrolyte chains that electrostatically bind to the quaternary ammonium −NH 4 + groups of the CTAB molecules initially present on the nanorods' surface, making them negatively charged.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Extinction spectra and ζ potential measurements (Figure 1e) confirmed the binding of PAA8k to the nanorod surface. There was a small blue shift in the extinction spectra (Figure 1a, blue), which was consistent with previous reports, 28,29 and the surface charge changed from +24.6 to −60.2 mV upon PAA8k coating. The reversal in the ζ potential sign is due to the presence of carboxylate −COO − groups in the polyelectrolyte chains that electrostatically bind to the quaternary ammonium −NH 4 + groups of the CTAB molecules initially present on the nanorods' surface, making them negatively charged.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…This is consistent with our previous observation on gold nanorods that undergo random aggregation at longer time durations if the surface charge is not increased to stabilize the assemblies. 29 The tip-specificity was also present with PAA8k-coated NBPs. However, we found that the relative orientation between the assembled NBPs was quite different from that of the PAA15kcoated NBPs under similar experimental conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The precipitation behavior of presynthesized oppositely charged nanoparticles has been investigated in millimeter-thick agarose gel. , Very recently, the precipitation behavior of silver nanoparticles (Ag NPs) has been studied by enabling the contact of agarose gel doped with silver ions with the surface of gelatin containing a reducing agent . Moreover, periodic patterns of plasmonic nanoparticles are of greater importance due to their application in surface plasmon resonance (SERS)-based sensors, electrochemical energy storage, and others. , In this work, commonly used polymer films, polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP), are chosen to investigate the pattern formation. The thickness of the film plays a critical role in controlling the diffusion time scale.…”
Section: Introductionmentioning
confidence: 99%
“…22 Moreover, periodic patterns of plasmonic nanoparticles are of greater importance due to their application in surface plasmon resonance (SERS)-based sensors, electrochemical energy storage, and others. 23,24 In this work, commonly used polymer films, polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP), are chosen to investigate the pattern formation. The thickness of the film plays a critical role in controlling the diffusion time scale.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the shielding effect of CTAB, most of the AuNR surface is relatively passivated in comparison to the two tips in motion. In terms of the AuNR assembly, the thiol and amino properties are used to selectively bind the tip of CTAB-stabilized AuNRs to induce the formation of tip-to-tip Au nanoaggregates. , Furthermore, preferentially etching the tips and shortening the CTAB-stabilized AuNRs cause a significant blueshift in the longitudinal surface plasmon resonance (LSPR) bands of the AuNRs. , Therefore, properly promoting or suppressing the shielding effects is of great significance for nanomaterial research, whether it is the size adjustment or the preparation of nanomaterials based on the CTAB-stabilized AuNRs. As a typical anisotropic metal nanostructure, the resonance frequency of the AuNRs is highly dependent upon the refractive index of the surrounding environment and the aspect ratio. , When the CTAB molecules around AuNRs are replaced by other stabilizer molecules, the change of LSPR can be used to observe this phenomenon intuitively.…”
Section: Introductionmentioning
confidence: 99%